A Paradigm for Comparative Historical Studies Between China and the West: Review of Nicolas Standaert's The Intercultural Weaving of Historical Texts: Chinese and European Stories - XIAO Qinghe, (Journal of Research for Christianity in China (JRCC), 2025)
This article reviews Professor Nicolas Standaert's new work, The Intercultural Weaving of Historical Texts: Chinese and European Stories (2016). This work represents Professor Nicolas Standaert's continuation of his previous research trajectory on Sino-Western cultural exchange, offering an outstanding synthesis and comparative study of historical texts from China and the West during the 17th and 18th centuries. The book meticulously examines an exceptionally rich array of historical documents from both cultures, presenting profound theoretical analysis. It not only enriches the body of research on the history of Sino-Western cultural exchange but also holds immense reference value for comparative historical studies and missionary sinology research.